Analysis of the results of the implementation of competence-based management model training for future high school teachers (Pedagogy of Higher and Secondary Education, 2014)
Drach І. І. Analysis of the results of the implementation of competence-based management model training for future high school teachers.The paper substantiates the need to update the administrative mechanisms in the implementation of competence-oriented training of future teachers in higher education. The results of the pedagogical experiment to introduce competence-based management model in preparation for graduate pedagogy of higher education are analyzed. The features of the dynamics of cognitive development, the activity and personal components of professional competence of future teachers in higher education are disclosed. Concluded due more pronounced dynamics of the formation of professional competence of students in the experimental groups compared with the control groups with the additional influence of the model developed competence-based management training pedagogy graduate high school.
Keywords: competence approach; competence-based management; training; professional competence